Maternal circulating levels of activin A, inhibin A, dFlt-1 and endoglin at parturition in normal pregnancy and pre-eclampsia - Reddy, A; Suri, S; Sargent, I; Redman, C; Muttukrishna, S (Public Library of Science, 2009)
Background: Maternal circulating levels of anti-angiogenic factors such as soluble fms-like tyrosine kinase-1 (sFlt-1), endoglin (sEng) and placental proteins like activin A and inhibin A are increased before the onset of pre-eclampsia. There is evidence for oxidative stress in pre eclampsia. Recently it was shown that placental oxygen concentration is related to sFlt-1 and inhibin A. In addition it is reported that oxidative stress markers are increased in placental tissue delivered after labour. Therefore, the objective of this study is to investigate if these proteins are altered in maternal circulation of labouring preeclampsia and normal pregnancies. Methodology: To assess the effects of labour, samples were taken from 10 normal pregnant (NP) and 10 pre-eclamptic (PE) women pre-labour, full dilation, placental delivery and 24 h. To assess the effects of placental delivery, plasma samples were taken from 10NP and 10PE women undergoing elective Caesarean section, pre-delivery, placental delivery and 10 min, 60 min and 24 h post delivery. SFlt-1 and sEng and activin A and inhibin A were measured using commercial and in house ELISA’s respectively. Results: The levels of sFlt-1 and sEng were significantly higher in PE compared to NP women in both groups. In labour, sFlt- 1 levels increased significantly at full dilatation in PE women, before declining by 24 hr. However there was no significant rise in sEng levels in labour. Activin A and inhibin A levels declined rapidly with placental delivery in NP and PE pregnancies. There was a significant rise in activin A levels during labour in PE compared to pre labour, but inhibin levels did not increase. Conclusion: Labour in pre-eclamptic women increases the levels of sFlt-1 and activin A. This pilot data suggests that increase in the maternal levels of these factors in labour could predict and/or contribute to the maternal syndrome postpartum.